2017
DOI: 10.19044/esj.2017.v13n24p156
|View full text |Cite
|
Sign up to set email alerts
|

Les Pathologies Chirurgicales Néonatales À l'Hôpital National De Lamordé De Niamey: Aspects Diagnostiques, Thérapeutiques Et Pronostiques

Abstract: Purpose: The purpose of this study is to describe the characteristics of the newborn and its surgical pathologies managed in the service of pediatric surgery of the National Hospital of Lamordé. Patients and Methods: It is a retrospective and descriptive study within a period of 10 years (from January 1st 2007 till December 31st 2016). The epidemiological, diagnostic, therapeutic, and evolutionary aspects were also studied. Results: The surgical pathologies of the newborn child represented 12.8 % of the hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Regarding operated patients, the digestive stoma is the most performed surgical procedure in the series. [ 3 8 ] In this series, its proportion is 49.4%. It is an effective, low-cost waiting surgical procedure that can be carried out in peripheral health facilities, making it possible to improve the long-term prognosis and reduce the mortality of certain digestive anomalies with neonatal exposure.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Regarding operated patients, the digestive stoma is the most performed surgical procedure in the series. [ 3 8 ] In this series, its proportion is 49.4%. It is an effective, low-cost waiting surgical procedure that can be carried out in peripheral health facilities, making it possible to improve the long-term prognosis and reduce the mortality of certain digestive anomalies with neonatal exposure.…”
Section: Discussionmentioning
confidence: 86%
“…The incidence of GIM found in our study is higher than that established by the WHO in 2010, which is 15% and varies by country. [ 1 9 ] Omid[ 3 ] explains these differences by the demographic characteristics of the populations and the specificities of pediatric surgical services depending on the country. Regarding the male predominance observed in newborns with GIM, we currently do not find an explanation for the male predominance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ndour et al [19] reported in their series an overall mortality rate of 45.3% (less prevalent in isolated defects). In one Nigerian study, omphalocele accounted for 18.3% of the neonatal surgical pathology and the rate post-operative mortality was of 26%, while it was of 15% in one Moroccan published study [5,42]. A new insight for the type II giant omphaloceles (defects greater than 5 cm or presence of liver) is the possible conservative management at birth with delayed surgical closure of the ventral hernia after [10].…”
Section: The Prognosismentioning
confidence: 99%